Is the definition of "permanent establishment" ("PE"), as used in the Double Tax Agreements ("DTA's") of selected Southern African Development Community ("SADC") countries, sufficient to protect their taxing rights over their natural resources? - Collop, Lance (College of Accounting, 2014)
This dissertation will determine whether or not the definition of a PE, as used in the DTAs of selected SADC countries, sufficiently protects the right these countries have to tax foreign companies or other non-resident taxpayers who use their natural resources profitably.